Fall-induced spinal cord injury: External causes and implications for prevention. (2nd January 2016) - Chen, Yuying; Tang, Ying; Allen, Victoria; DeVivo, Michael J
Abstract : Objective : To document the demographic and clinical profile of persons who sustained spinal cord injury (SCI) as a result of accidental falls and to determine the usual circumstances surrounding the fall-induced SCI. Design : Cohort study. Setting : 21 SCI Model Systems centers throughout the United States. Participants : 6, 408 individuals with traumatic SCI between 2005 and 2014 were recruited from the National SCI Database. 1, 877 (29%) of them were injuries caused by falls. Interventions : Not applicable. Outcomes Measures : External causes of injury documented by the International Classification of Diseases, 10 th revision, Clinical Modification (ICD-10-CM). Results : Falls on the same level from slipping, tripping, and stumbling were the most common cause of fall-induced SCI (20%), followed by falls from building (16%), stairs and steps (16%), and ladder (9%). People who were 61 years of age and older had the highest frequency of falls on the same level, while those aged 16–45 years had a higher percentage of falls from buildings, usually work-related. The mechanisms of falls also varied by sex and race. Associated injury and vertebral injury occurred frequently among falls from buildings and ladders. High falls were more likely to be work-related and result in thoracic and complete injury, while low falls were more commonly associated with cervical and motor functionally incomplete injury. Conclusion : The study findings of different mechanisms of falls by age, sex, race and medical consequences provide an insight for future interventions aimed at high risk persons, activities, and environmental factors for preventing or reducing fall-induced SCI.